Hz : a speculation into the future of sounds in the age of Anthropocene - Sim, Sheryl Zhi Ning (Nanyang Technological University, 2020)
Hz is an interactive sonic art installation that explores how people connect with Nature in the city today and beyond through sensorial experiences. The work suggests the sounds of a city and how they evolve with humans and machines in this age of the Anthropocene, presenting them with sculptures of mediated Nature. With human’s dominant force on the environment, they have significant influence over the mix of sounds heard today. Urban living has resulted in an overpopulation of sounds; the sounds of the natural world end up mixing and competing with the sounds of the built environment, composing a soundscape that gets louder and more confusing as the line between the natural and the synthetic gets increasingly blurred. With this being the future of sounds, Hz seeks to understand and rationalise their coexistence. Hz explores how Biophony, the sounds of the natural environment, is affected by Anthrophony, as it becomes more and more unnatural. However, what is natural? Being so familiar with the aural ecology of the city, is this really so strange? How do city dwellers then come to terms and respond to this evolving soundscape, and how does this affect them? Interactive Media Key Words: Anthropocene, Man & Nature, Machine, Technological Nature, Sound Art, Sound installation, Listening